2022
DOI: 10.1370/afm.2762
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians’ Core Needs in a Pandemic: Qualitative Findings From the Chat Box in a Statewide COVID-19 ECHO Program

Abstract: PURPOSEResearch on primary care's role in a pandemic response has not adequately considered the day-to-day needs of clinicians in the midst of a crisis. We created an Oregon COVID-19 ECHO (Extension for Community Healthcare Outcomes) program, a telementoring education model for clinicians. The program was adapted for a large audience and encouraged interactivity among the hundreds of participants via the chat box. We assessed how chat box communications within the statewide program identified and ameliorated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Throughout the coronavirus disease 2019 (COVID-19) pandemic, family physicians faced challenges associated with travel restrictions for patients, lockdowns, quarantine, gaps in testing infrastructure, lack of PPE supply, and calls to provide clinical services to testing centres, vaccination sites, and long-term care settings [ 1 – 3 ]. In nearly every aspect of their work, family physicians felt pressure as a result of having to integrate evolving public health guidelines around social distancing and infection control measures such as masks and hand hygiene [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the coronavirus disease 2019 (COVID-19) pandemic, family physicians faced challenges associated with travel restrictions for patients, lockdowns, quarantine, gaps in testing infrastructure, lack of PPE supply, and calls to provide clinical services to testing centres, vaccination sites, and long-term care settings [ 1 – 3 ]. In nearly every aspect of their work, family physicians felt pressure as a result of having to integrate evolving public health guidelines around social distancing and infection control measures such as masks and hand hygiene [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the coronavirus disease 2019 (COVID-19) pandemic, family physicians have faced challenges associated with travel restrictions, lockdowns, quarantine, gaps in testing infrastructure, lack of PPE supply, and calls to provide clinical services to testing centres, vaccination sites, and long-term care settings. (1)(2)(3) In nearly every aspect of their work, family physicians felt pressure as a result of having to integrate evolving public health guidelines around social distancing and infection control measures such as masks and hand hygiene. (4) COVID-19 has also led to substantial changes to the practice of medicine, including the need to conduct assessments and provide health education virtually, and the need to provide testing and immunizations with distancing measures in place.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to seeking reliable information and practical tools related to COVID-19 response, clinicians expressed a need for support and connection. 5 In a qualitative study, Kelly et al found that staff members in a primary care clinics pulled together to respond to the acute reorganization in response to the pandemic. Staff contributed by learning new skills and taking on new roles during the early months of the pandemic.…”
mentioning
confidence: 99%